2016
DOI: 10.2119/molmed.2016.00082
|View full text |Cite
|
Sign up to set email alerts
|

Emetine Di-HCl Attenuates Type 1 Diabetes Mellitus in Mice

Abstract: Type 1 diabetes mellitus (T1D) is a chronic autoimmune disease characterized by β cell destruction, insulin deficiency and hyperglycemia. Activated macrophages and autoimmune T cells play a crucial role in the pathogenesis of hyperglycemia in NOD murine diabetes models, but the molecular mechanisms of macrophage activation are unknown. We recently identified pigment epithelium-derived factor (PEDF) as an adipocyte-derived factor that activates macrophages and mediates insulin resistance. Reasoning that PEDF mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Carbenoxolone can also act as the inhibitor of Pannexin 1 (Panx-1) and suppress the migration and invasion of testicular cancer cells to counter cancer progression and metastasis (Penuela et al, 2012;Furlow et al, 2015;Jankowski et al, 2018;Liu et al, 2019). Emetine, a potent anti-protozoal and emetic drug, recent evidence has verified its anti-malarial, anti-bacterial and anti-amoebic effects (Matthews et al, 2013;Hudson et al, 2016;Khandelwal et al, 2017;Yang et al, 2018). Over the past decades, emetine has been reported to have anti-tumor effects on leukemia, ovarian cancer, bladder cancer and lung cancer by inhibiting tumor growth by regulating multiple mechanisms such as apoptosis and autophagy Kim et al, 2015;Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Carbenoxolone can also act as the inhibitor of Pannexin 1 (Panx-1) and suppress the migration and invasion of testicular cancer cells to counter cancer progression and metastasis (Penuela et al, 2012;Furlow et al, 2015;Jankowski et al, 2018;Liu et al, 2019). Emetine, a potent anti-protozoal and emetic drug, recent evidence has verified its anti-malarial, anti-bacterial and anti-amoebic effects (Matthews et al, 2013;Hudson et al, 2016;Khandelwal et al, 2017;Yang et al, 2018). Over the past decades, emetine has been reported to have anti-tumor effects on leukemia, ovarian cancer, bladder cancer and lung cancer by inhibiting tumor growth by regulating multiple mechanisms such as apoptosis and autophagy Kim et al, 2015;Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that the application of emetine restrained TNF level and insulitis in diabetes mellitus mouse. 22 However, the role of emetine in DN has not been clearly clarified.…”
Section: Introductionmentioning
confidence: 99%